Low-Dose Copper Exposure Exacerbates Depression-Like Behavior in ApoE4 Transgenic Mice - Xu, Jia; He, Kaiwu; Zhang, Kaiqin; Yang, Chao; Nie, Lulin; Dan, Ding; Liu, Jianjun; Zhang, Chang-E.; Yang, Xifei (Oxidative medicine and cellular longevity, 2021)
Depression is one of the most common neuropsychiatric disorders. Although the pathogenesis of depression is still unknown, environmental risk factors and genetics are implicated. Copper (Cu), a cofactor of multiple enzymes, is involved in regulating depression-related processes. Depressed patients carrying the apolipoprotein ε4 allele display more severe depressive symptoms, indicating that ApoE4 is closely associated with an increased risk of depression. The study explored the effect of low-dose Cu exposure and ApoE4 on depression-like behavior of mice and further investigates the possible mechanisms. The ApoE4 mice and wild-type (WT) mice were treated with 0.13 ppm CuCl2 for 4 months. After the treatment, ApoE4 mice displayed obvious depression-like behavior compared with the WT mice, and Cu exposure further exacerbated the depression-like behavior of ApoE4 mice. There was no significant difference in anxiety behavior and memory behavior. Proteomic analysis revealed that the differentially expressed proteins between Cu-exposed and nonexposed ApoE4 mice were mainly involved in the Ras signaling pathway, protein export, axon guidance, serotonergic synapse, GABAergic synapse, and dopaminergic synapse. Among these differentially expressed proteins, immune response and synaptic function are highly correlated. Representative protein expression changes are quantified by western blot, showing consistent results as determined by proteomic analysis. Hippocampal astrocytes and microglia were increased in Cu-exposed ApoE4 mice, suggesting that neuroglial cells played an important role in the pathogenesis of depression. Taken together, our study demonstrated that Cu exposure exacerbates depression-like behavior of ApoE4 mice and the mechanisms may involve the dysregulation of synaptic function and immune response and overactivation of neuroinflammation.